SCIENTIFIC ATTITUDES TOWARDS AN EASTERN MYSTIC - Alberta (Journal of Dharma, 1996)
Sri Ramakrishna, a nineteenth century Hindu mystic, long a subject of considerable interest for Western theorists, may be categorized as a "crazy saint" (Feuerstein 1990), along with many other figures, such as Joan of Arc, St. Francis of Assisi, Mahaprabhur and Sri Caitanya, to name only a few. Mystics such as these, and their unusual behaviour, have been known to be surrounded by substantial controversy in every cultural, political, social, and religious context throughout the world.